Unmasking Buddhism - Faure, Bernard (Wiley-Blackwell, 2009)
Buddhism in history -- Buddhism is both one and many at the same time -- The Buddha is only a man who achieved awakening -- Buddhism is an Indian religion -- Buddhism is the cult of nothingness -- Buddhism is a philosophy, not a religion -- All Buddhists are seeking to achieve awakening -- Buddhism teaches the impermanence of all things -- The belief in karma leads to fatalism -- Buddhism denies the existence of a self -- Buddhism teaches reincarnation -- Buddhism and local cultures -- Buddhism is an atheistic religion -- Buddhism is above all a spirituality -- The Dalai Lama is the spiritual leader of Buddhism -- To be Buddhist is to be Zen -- Buddhism and society -- Buddhism is a tolerant religion -- Buddhism teaches compassion -- Buddhism is a peaceful religion -- Buddhism affirms that we are all equal -- Buddhism is compatible with science -- Buddhism is a kind of therapy -- Buddhism advocates a strict vegetarianism -- Buddhism is a universalist teaching -- Buddhism is a religion detached from the world -- Conclusion: Buddhism or neo-Buddhism?